2020
DOI: 10.1186/s12911-020-01182-2
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an EMR algorithm to measure the prevalence of ADHD in the Canadian Primary Care Sentinel Surveillance Network (CPCSSN)

Abstract: Background: Building and validating electronic algorithms to identify patients with specific disease profiles using health data is becoming increasingly important to disease surveillance and population health management. The aim of this study was to develop and validate an algorithm to find patients with ADHD diagnoses within primary care electronic medical records (EMR); and then use the algorithm to describe the epidemiology of ADHD from 2008 to 2015 in a Canadian Primary care sample. Methods: This was a cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(47 citation statements)
references
References 29 publications
2
37
2
Order By: Relevance
“…Few studies have reported on the accuracy of ADHD diagnoses in healthcare utilization data, with PPVs generally consistent with our estimate, accounting for the width of the confidence interval 16,25,27,28 . One study reported that inclusion of patients with ≥1 ADHD‐medication prescription without a documented diagnosis did not yield any additional confirmed cases 25 .…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Few studies have reported on the accuracy of ADHD diagnoses in healthcare utilization data, with PPVs generally consistent with our estimate, accounting for the width of the confidence interval 16,25,27,28 . One study reported that inclusion of patients with ≥1 ADHD‐medication prescription without a documented diagnosis did not yield any additional confirmed cases 25 .…”
Section: Discussionsupporting
confidence: 81%
“…Excluding these 10 cases increased the PPV from 88% to 95%. Similar to these findings, a recent study by Morkem et al using a sample from one local clinic within the Canadian Primary Care Sentinel Surveillance Network reported a PPV of 95.9% (92.6%–98.0%) when requiring either 1 diagnostic code and ≥ 1 ADHD‐medication prescription or ≥ 2 encounters with a diagnostic code 27 . Thus, depending on the research question and the relative importance of high specificity versus sensitivity, using a more conservative definition (≥2 ADHD‐related encounters or 1 encounter and ≥ 1 prescription) might be the preferred approach.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…A total of ten papers are included in the review [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], all of which were published from 2012 to 2022 (see Table 1 ). Ten papers included prevalence estimates of ADHD in Canada [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Out of these papers, one also examined the incidence of ADHD in Canada [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…This group of studies based estimates on data collected from 1999 [ 11 , 20 ] to 2015/6 [ 12 , 17 , 20 ]. The range for data collection was similar for papers that focused on ADHD prevalence in children and/or adolescents (1999–2015/6) [ 11 , 15 , 17 , 18 , 20 ] and those that examined prevalence in adults (1999–2018) [ 13 , 14 , 15 , 16 , 19 ].…”
Section: Resultsmentioning
confidence: 99%